A Critical Evaluation of Environmental Dispute Resolution Mechanisms in Bangladesh - Uddin, Md. Ala (Faculty of Law, University of Jember, Indonesia, 2023)
Pollution is now the greatest dangerous threat to humanity. Nowadays, everyone scares pollution more than nuclear blasts. Human well-being and economic prosperity have made environmental conservation a critical global issue. Bangladesh is dealing with a number of environmental issues, including deforestation, land degradation, air pollution, water contamination, and biodiversity loss. In Part II (Fundamental Principles of State Policy) of the Bangladesh Constitution, Article 18A states,